Price Fluctuations and Social Media: A Study of Teenagers' Adaptive Consumer Choices - Azzahra, Anandita Salsabila; Yiğitsoy, Ezgi; Ulutürk, Zeynep Sena; Tresna, Pratami Wulan; Chan, Arianis; Barkah, Cecep Safa'atul (Universitas Muhammadiyah Sorong, 2024)
While experiencing hyperinflation, teenager needs to adjust and reevaluate their choices especially when they witness large price fluctuations and unexpected changes in their financial situation. Furthermore, they tends to focus on what’s happening on their social media. The main aim of this research is to examine how society behaved during the hyperinflation period in Türkiye using Bourdieu's theoretical framework. According to our research conducted through in-depth interviews and netnography, teenagers use three coping mechanisms to overcome their levels of cultural and economic capital. They often use coping mechanisms to create their own culture that helps them maintain their identity. This can help better understand behavior & habits of teenager buyers, especially in high inflation environments.